Social Construction of Public Administration in Indonesia - Pandhu Yuanjaya (Yogyakarta State University, 2020)
This study aims to discuss social construction in public administration in Indonesia. This is important because various studies show that the practice of public administration in Indonesia is still full of corruption, policy failures and the inability to solve problems. This research is a qualitative research. The data in this study were obtained from a literature review. The results of the study indicate that the failure of public administration practices in Indonesia is because the concept of public administration from developed countries is not adopted in the Indonesian social context. There are three factors, namely the general environment, the special environment, and the structure and culture of the bureaucracy. In an effort to become a centric Indonesia, Indonesia needs to make fundamental changes in adapting local socio-cultural conditions to public administration. Need to explore and develop local genius in creating concepts and practices of Indonesian public administration.